2016
DOI: 10.1111/ctr.12711
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐transplant phospholipase A2 receptor autoantibody concentration is associated with clinically significant recurrence of membranous nephropathy post‐kidney transplantation

Abstract: Previous studies that have assessed the association of pre-transplant antiphospholipase A2 receptor autoantibody (PLA2R-Ab) concentration with a recurrence of membranous nephropathy (rMN) post-kidney transplant have yielded variable results. We tested 16 consecutive transplant patients with a history of iMN for pre-transplant PLA2R-Ab. Enzyme-linked immunosorbent assay titers (Euroimmun, NJ, USA) >14 RU/mL were considered positive. A receiver operating characteristic (ROC) analysis was performed after combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…4 -6 Therefore, measurement of anti-PLA2R1 antibodies is useful for diagnosis, individual risk assessment, and monitoring of treatment in patients with MN, including the time after transplantation. [7][8][9][10] The prevalence of THSD7A-associated MN is significantly lower compared with that of PLA2R1-associated MN, and the clinical usefulness of anti-THSD7A autoantibody measurement is currently under investigation. 11 Noteworthy, 20% of white patients with THSD7A-associated MN have concurrent malignancies, suggesting that intensive screening for malignancies is advised in these patients.…”
mentioning
confidence: 99%
“…4 -6 Therefore, measurement of anti-PLA2R1 antibodies is useful for diagnosis, individual risk assessment, and monitoring of treatment in patients with MN, including the time after transplantation. [7][8][9][10] The prevalence of THSD7A-associated MN is significantly lower compared with that of PLA2R1-associated MN, and the clinical usefulness of anti-THSD7A autoantibody measurement is currently under investigation. 11 Noteworthy, 20% of white patients with THSD7A-associated MN have concurrent malignancies, suggesting that intensive screening for malignancies is advised in these patients.…”
mentioning
confidence: 99%
“…15,22 Antibodies against PLA2R, LPLUNC, APMAP, and PRKCZ were described previously in small case-series and have not been further evaluated. [23][24][25] During the development of our non-HLA antibody assay we found that MFI results on a specific bead was comparable between singleplex and multiplex measurement, indicating no occurrence of compromise by multiplex analysis. In general, non-HLA antibodies frequently occur within the healthy population and for many autoantibodies a serum is considered positive when exceeding a cut-off yielding a limited (<5%) frequency of positive results within the healthy population.…”
Section: Discussionmentioning
confidence: 82%
“…In one study of seven patients with rMN, six had at‐risk HLA‐DQ alleles, the presence of which was significantly associated with pretransplant PLA2R antibody levels . Another study found that four of five patients with rMN had at‐risk HLA‐DQ alleles, as compared to five of nine without recurrence, but this was nonsignificant ( P =.6) …”
Section: Membranous Nephropathy In the Native Kidneymentioning
confidence: 99%
“…Likewise, Gupta et al . studied 16 patients with pMN consecutively transplanted at the University of Virginia.…”
Section: Recurrent Membranous Nephropathymentioning
confidence: 99%
See 1 more Smart Citation